The Effectiveness of Counselling and Educational Videos on the Knowledge and Attitudes of Adolescents About Early Marriage in Asy-Syukur Junior High School Plus - Marits Maqsyalina; Riza Yuliawati (Universitas STRADA Indonesia, 2025)
Early marriage generally causes many problems both physically and mentally, especially with socio-economics. According to the Office of Women's Empowerment, Child Protection, Population Control and Family Planning of Blitar Regency throughout 2022, there were 168 applications for marriage dispensation in Blitar Regency, while for 2023 recorded until May 2023 there were 108 application data. The purpose of this study was to determine the effectiveness of counselling and educational videos on the knowledge and attitudes of early marriage in adolescents. This research design is Pre-Experimental Designs, this type of research combines Pretest and Posttest Study with a sample size of 40 respondents. Data analysis using Paired Sample T Test. There is a significant difference in the average results of knowledge of early marriage in adolescents between before and after giving counselling and educational videos with a value of r Count 4.995 and p-value = 0.000 (<0.05). And there is a significant difference in the average results of early marriage attitudes in adolescents between before and after the provision of counseling and educational videos with a value of r Count 6.019 and p-value = 0.000 (<0.05), meaning that there are differences in knowledge and attitudes of early marriage before and after the intervention of counseling and educational videos on adolescents at Asy-Syukur Junior High School Plus. It is important to learn about the impact of early marriage on adolescents, so that adolescents can achieve understanding and understand about themselves in relation to the problems they face later, especially the problem of early marriage.